Use of Learning Media in Supporting Health Education in Early Children - Nurjanah, Eva; Aulia K, Qisthi; Zulfah, Wafa; Shintiarani, Livia; Tutiana, Siska; Barokah, Wawam; Nurazizah, Indriani; Nurbayinah, Pajwah Siti; A, Mushlih Kamal; Istia’dah, Feida Noor Laila (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Early childhood is a golden period where at this time the child's brain ability to think is growing rapidly up to 80%. The provision of health education to early childhood is very good because it has a great opportunity to become a healthy habit in the next stage of life. Providing education from an early age about children's health, especially how to brush their teeth properly can prevent dental caries. Getting used to washing hands with soap in children can prevent the occurrence of diseases caused by bacteria, such as diarrhea, typhoid, and so on. Learning media will help the effectiveness of the learning process in delivering messages and educational content provided. The purpose of this activity is to improve the health status of pre-school age children through health education about brushing teeth properly and washing hands with soap. This activity was carried out on pre-school age children at RA Al-Basyariyah, Pameungpeuk Village, Garut Regency. As a result of this community service activity, all pre-school children were able and enthusiastic in practicing the 6 steps of washing their hands and brushing their teeth correctly. Pre-school children are also able to answer questions given about the importance of brushing teeth and washing hands.